Determinants and impacts of communicable diseases on health outcome and economic growth in Nigeria - Chibueze, Onyechege Declan (2021)
The Nigerian government has implemented various measures to curtail the high prevalence of communicable diseases. The healthcare industry in Nigeria is working tirelessly to address this concern, but all the undertaken efforts seem fruitless. The fruitless efforts has motivated the researcher to investigate the socioeconomic determinants of communicable diseases in Nigeria. Hence, the first objective of this thesis is to explore the socioeconomic factors (income, education, savings, and final consumption expenditure) related to communicable diseases in Nigeria. The second objective of this thesis is to identify the impacts of communicable diseases on the health outcome in Nigeria. The poor economic outcome in Nigeria is a result of low health outcomes contributed by the high prevalence of communicable diseases in Nigeria. Thus, the third objective of this thesis is to investigate the impacts of communicable diseases on economic growth conditioned on health outcomes. This study was analysed using the Auto Regressive Distributed Lag (ARDL) model for all the study's objectives. The data collected for this study were secondary and obtained from reliable and other reputable agencies. The period of data estimation was 34 years, ranging from 1985 to 2018. Based on the study's findings, the socioeconomic determinants used in the first objective, proved significant in the HIV/AIDS model. Income proved a significant negative relationship at 1% with HIV/AIDS, while savings, education, and final consumption expenditure had a significant positive relationship with HIV/AIDS at 1%, 10%, and 1%, respectively. For the Tuberculosis model, all the socioeconomic determinants had a positive relationship with Tuberculosis. Nevertheless, only savings and final consumption expenditure were significant at 5% and 10%, respectively. For the second objective, the result proved that HIV/AIDS, had a negative relationship with life expectancy at a 10% significant level. Contrarily, Tuberculosis had an insignificant negative relationship with life expectancy. For the under-5 mortality rate (UMR) model, HIV/AIDS proved to have an insignificant negative relationship with UMR, while Tuberculosis proved to have a positive relationship with UMR, which was significant at a 1% level. The third objective study's findings proved an insignificant positive relationship between health outcomes and economic growth. In addition, communicable diseases had significant impacts on economic growth at a 1% significant level in consideration of the interactive variables at minimum, maximum, and mean values of the conditioned variables. In conclusion, the low-income level of Nigerians has been alarming in recent years. An increase in income reduces the prevalence of communicable diseases. The Nigerian government should put more effort into equity in income, a balanced flow of income should be favourable to all citizens. And this can be achieved by increasing workers' minimum wages. Secondly, the Nigerian government should strive to implement free medical care access for its citizens, by providing good medical care services mainly to the people at the grassroots, where communicable diseases are increasing. The dependence on foreign financial assistance can be reduced if Nigeria can improve the local sectors by giving support to the production capacity of these local sectors hence creating employment opportunities for Nigerians.